2016
DOI: 10.5194/amt-9-4601-2016
|View full text |Cite
|
Sign up to set email alerts
|

A laser-induced fluorescence instrument for aircraft measurements of sulfur dioxide in the upper troposphere and lower stratosphere

Abstract: Abstract. This work describes the development and testing of a new instrument for in situ measurements of sulfur dioxide (SO 2 ) on airborne platforms in the upper troposphere and lower stratosphere (UT-LS). The instrument is based on the laser-induced fluorescence technique and uses the fifth harmonic of a tunable fiber-amplified semiconductor diode laser system at 1084.5 nm to excite SO 2 at 216.9 nm. Sensitivity and background checks are achieved in flight by additions of SO 2 calibration gas and zero air, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…An in situ instrument based on a laser‐induced fluorescence (LIF) technique was used in this study to achieve the desired sensitivity for SO 2 mixing ratios on the order of 1 part per trillion (pptv, 10 −12 number mixing ratio) and to afford operation onboard the NASA WB‐57F high‐altitude research aircraft [ Rollins et al , ]. The instrument excites SO 2 by using a tunable laser near 216.9 nm and detects the resulting red‐shifted fluorescence at 240–400 nm.…”
Section: Methodsmentioning
confidence: 99%
“…An in situ instrument based on a laser‐induced fluorescence (LIF) technique was used in this study to achieve the desired sensitivity for SO 2 mixing ratios on the order of 1 part per trillion (pptv, 10 −12 number mixing ratio) and to afford operation onboard the NASA WB‐57F high‐altitude research aircraft [ Rollins et al , ]. The instrument excites SO 2 by using a tunable laser near 216.9 nm and detects the resulting red‐shifted fluorescence at 240–400 nm.…”
Section: Methodsmentioning
confidence: 99%
“…SO 2 is removed from the atmosphere primarily by homogeneous and heterogeneous oxidation with a characteristic lifetime of one to two days (Langner & Rodhe, 1991;Wojcik & Chang, 1997) to form sulfuric acid (H 2 SO 4 ) and sulfate (SO 4 2À ), therefore, contributing to new particle formation (Sipila et al, 2010) as well as the acidity of precipitation (Hegg & Hobbs, 1981) and aerosols (Weber et al, 2016). SO 2 as well has been measured extensively by mass spectrometry (Huey et al, 1995Jurkat et al, 2010;Kim et al, 2007;Miake-Lye et al, 1998;Mohler et al, 1992;Seeley et al, 1997;Slusher et al, 2004;Speidel et al, 2007;Thornton et al, 2002) but is most commonly measured utilizing fluorescence (Luke, 1997;Matsumi et al, 2005;Okabe et al, 1973;Rollins et al, 2016;Schwarz et al, 1974;Simeonsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pulse-pair resolution is greater than the signal lifetime the system will at most count one fluorescent photon per laser shot and therefore at very high signal levels the observed count rate will start to deviate from a linear response to the rate at which photons strike the photocathode. However, as discussed previously (Wennberg et al, 1994;Rollins et al, 2016) under the conditions of a known maximum count rate (320 kHz) the observed count rate can be corrected exactly to match the true signal rate and thereby significantly increase the dynamic range without loss of accuracy. At the present typical signal rates (∼ 10 counts s −1 pptv −1 ), errors associated with saturation would not be encountered for NO less than 100 ppbv.…”
Section: Linearitymentioning
confidence: 99%
“…The laser and optical detection system used here are based on that originally described by Rollins et al (2016) for measurements of sulfur dioxide. Subsequent to that work, important changes have been made to the design of the fiber laser system, and therefore a complete description is provided here.…”
Section: Instrument Descriptionmentioning
confidence: 99%